Change in Heart Rate Variability After the Adult Attachment Interview in Dissociative Patients. Issue 2 (15th March 2015) - Farina, Benedetto; Speranza, Anna Maria; Imperatori, Claudio; Quintiliani, Maria Isabella; Marca, Giacomo Della
Abstract : The aim of this study was to assess heart rate variability (HRV) in individuals with dissociative disorders (DD) before and after the Adult Attachment Interview (AAI). Electrocardiograms were recorded before, during, and after the AAI in 13 individuals with DD and 13 healthy participants matched for age and gender. Significant change in HRV was observed only in the DD group. After the AAI, those with DD showed significant increases in the low frequency/high frequency ratio (pre-AAI = 1.91 ± 1.19; post-AAI = 4.03 ± 2.40; Wilcoxon test = –2.76, p = .005). Our results suggest that the retrieval of childhood attachment experiences in individuals with DD is associated with a change in HRV patterns that could reflect the emotion dysregulation of dissociative psychopathological processes.